Ampliação vocabular para as práticas sociais de alunos deficientes intelectuais - Naves, Mariana Silva (2020)
Our research aims to carry out a proposal of pedagogical intervention that can expand the lexical collection of students with intellectual disabilities, who are attended in Portuguese language classes of regular education in the multifunctional resources room of AEE - Specialized Educational Service, which serve students with that profile. The specific objectives is: (i) to develop some activities in the AEE classes focused on lexical expansion work; (ii) evaluate the pertinence of the applied activities and, subsequently, reformulate them; (iii) to contribute so that students can expand their active lexicon in a more reflective way and that meets their social demands; (iv) develop an application that contains one of the proposed activities so that it can be used in the two learning environments: common room and AEE. We turn to studies of semantic-lexical variation with a focus on the parasynonym, in order to stimulate the interest and desire of our students to learn in a more fun and entertaining way. Our research allows us to reflect about the inclusion of students with intellectual disabilities, how important it is to discuss possibilities of intervention that are effective for a greater understanding of their linguistic universe, and how much Lexicology can contribute to this process. Thus, based on theoretical research on the cognitive universe of students with intellectual disabilities and on the semantic-lexical variation, we seek to build a theoretical contribution that can subsidize native language teachers to develop pedagogical intervention activities aimed at the lexical expansion of students who meet this profile. The theoretical basis for the discussions was based mainly on the following researchers: Barbosa (1978; 1990; 1997); Cançado (2013); Coseriu (1979; 1980); Mantoan (2003); Vigotsky (2006), Faraco (2008; 2012), Preti (2003), among others. The action research, here methodologically subsidizing our work, allowed the discussions about the linguistic development of students with intellectual disabilities to broaden, in addition to developing greater criticality in the elaboration of activities aimed at teaching and lexical expansion.